Watching social media and its impact on children’s family communication: field study - BENKIHOUL, Mohamed; ALLOUTI , Achour (Journal of Human Sciences, 2025)
The current study aims to reveal the impact of watching social media on children’s family communication, as a field study in the city of Ain El Melh, where the study sample consisted of 30 families of children who were chosen randomly. Based on that, we are trying through this study to answer the following general question: - To what extent does watching social media affect children’s family communication? Which includes the following sub-questions: - To what extent does social media time affect children’s family communication? - To what extent does frequent viewing of social media affect children’s family communication? - To what extent does the absence of parental control over the quality of programs viewed affect children’s family communication?